MANAGING CUSTOMER RELATIONSHIP IN PRIORITYBANKING – TIPCE AS DRIVER OF CUSTOMER LOYALTYAND WORD OF MOUTH OF PT BANK MANDIRI. CASE STUDY OF PRIORITY BANKING CUSTOMERS IN KELAPA GADING. - Fidelia Pramesti (Fakultas Ekonomi & Bisnis Universitas Paramadina, 2019)
This research proposes the idea of applying company culture or philosophy into a set of operation procedure which is applied by all employees. The goals of implementing company culture into a set of procedure are obtain long term profitability by creating loyalty behavioral intention and positive word of mouth from the existing customers. The sample used in this research is priority banking customers in PT Bank Mandiri Indonesia that is located inKelapaGading Priority Outlet. It is founded that customers will generate word of mouth based on what they feel about the bank. In addition, they will remain loyal with the bank if they feel satisfied with the services.Keyword: Relationship marketing, word of mouth, loyalty behavioral intention.